Acute kidney injury observed during phase 1 clinical trials of a novel xanthine oxidase/URAT1 dual inhibitor PF-06743649. Issue 8 (August 2016) - Dua, Pinky; Gurrell, Rachel; Kirby, Simon; Sudworth, Maria; Loudon, Peter
Abstract The objective of these clinical studies was to assess the safety and urate lowering activity of a novel urate transporter 1 (URAT1)/ xanthine oxidase (XO) inhibitor PF-06743649 in healthy subjects and gout patients. Escalating doses of PF-06743649 or placebo were given to healthy young subjects, healthy elderly subjects and gout patients. Serum uric acid (sUA) and urinary pharmacodynamic markers were assayed, and safety was assessed by collection of adverse events and assessment of safety labs, ECGs and vital signs. Administration of PF-06743649 led to rapid decrease in sUA in all cohorts; in gout patients, a change from baseline of 69 % was observed for the 40 mg dose. Urinary and serum biomarkers were consistent with inhibition of both URAT1 and XO. Although dosing was otherwise well tolerated, two subjects experienced serious adverse events of acute kidney injury. Both subjects exhibited increased serum creatinine and blood urea nitrogen in the first 3 days post first dose and were hospitalised. One subject exhibited oliguria for the first 24 h. Both subjects made a complete recovery with minimal intervention. PF-06743649 was effective at rapidly lowering sUA, but further development was terminated for an identified renal safety risk.